An Overview of Young Adults' Opinions into Cyber Relation: Turkey Sample. (13th May 2015) - Demirtas-Zorbaz, Selen; Genctanırım, Dilek; Kurt, Akıp
Abstract: Social media consumption is increasing in Turkey day by day as in whole word. Nowadays, individuals contact with emotional attachment and have romantic relations with people who they meet on internet and social media. People's perception and their messages to those who have online relationship could affect the relationship's quality. Aim of this study is to determine the opinions of young adults about cyber relations that contacted with social media. 244 volunteer young adults participated in the present study. The sample was comprised of 85 female, and 55 male. Young adult's perception of cyber romantic relationship was discussed according to literature.